ORGANOLEPTIC INDICATORS OF WATER, THEIR FORMATION FACTORS, AND SANITARY ASSESSMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This study examines organoleptic parameters of potable water from urban distribution systems through standardized sensory evaluation methods. Analysis of 240 samples revealed mean turbidity of 1.8±0.4 NTU, color values of 12±3 degrees, and temperature-dependent odor variations. Results demonstrate critical relationships between organoleptic deviations and anthropogenic contamination patterns requiring enhanced monitoring protocols.